Semantisk isotopi og diskursanalyse - Frandsen, Finn (HERMES - Journal of Language and Communication in Business, 1988)
Even though the notion of semantic isotopy is being extensively used within the analysis of both literary texts and special-purpose texts, the theoretical problems yet unsolved are legion. In this article I first demonstrate the great relevance of this notion for discourse analysis and then give a survey of Greimas' classical definitions of semantic isotopy and the previous critique of this conception. Finally, I evaluate Rastier's reformulation of semantic isotopy from the point of view of interpretative semantics.